Tārīkh futūḥ al-Shām. - Azdī, Muḥammad ibn ʻAbd Allāh, -approximately 781, author.
1 online resource.
Keywords: "This book narrates the battles, conquests and diplomatic activities of the early Muslim fighters in Syria and Iraq vis-à-vis their Byzantine and Persian counterparts. It is the first English translation of one of the earliest Arabic sources on the early Muslim expansion entitled Futūḥ al-Shām (The Conquests of Syria). The translation is based on the Arabic original composed by a Muslim author, Muḥammad al-Azdī, who died at the turn of the 8th to the 9th century C.E. A scientific introduction to al-Azdīʼs work is also included, covering the life of the author, the textual tradition of the work as well as a short summary of the textʼs train of thought. The source narrates the major historical events during the early Muslim conquests in a region that covers today's Lebanon, Israel, Palestinian Territories, Jordan, Syria, Turkey and Iraq in the 7th century C.E. Among these events are the major battles against the Byzantines, such as the Battles of Ajnādayn and al-Yarmūk, the conquests of important cities, including Damascus, Jerusalem and Caesarea, and the diplomatic initiatives between the Byzantines and the early Muslims. The narrative abounds with history and Islamic theological content. As the first translation into a European language, this volume will be of interest to a wide range of readership, including (Muslim and Christian) theologians, historians, Islamicists, Byzantinists, Syrologists and (Arabic) linguists"--